Evaluation of the Zoning System for New Students of State High Schools in the Special Region of Jakarta - Bakti, Rizal; Nahdiana, Nahdiana; Sukaesah, Isoh; Suryandari, Arum Puri; Fidyanti, Ammy; Agustini, Agustini (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to evaluate the implementation of the zoning system for new student admissions (PPDB) in public senior high schools in the Special Capital Region of Jakarta from 2022 to 2024, with a focus on the role of school principals in executing the policy. Employing a quantitative approach with an evaluative design, the research assesses the effectiveness, fairness, and challenges of the zoning system. The population of the study consists of 119 high school principals across four cities in the Jakarta region. Using stratified random sampling, the entire population was involved as the research sample. Data were collected through structured interviews and questionnaire instruments distributed to the principals. Additionally, supporting data from the Jakarta Education Office and related literature were used to strengthen the analysis. The collected data were processed using SPSS software to test the validity and reliability of the instruments and to perform descriptive statistical analysis. The findings show that while the zoning system has succeeded in promoting equal access to education, several challenges persist, including uneven school quality, limited capacity in certain zones, and a lack of socialization among stakeholders. Most principals agree that improvements are needed in policy implementation, especially in ensuring transparency and infrastructure readiness. The study concludes that although the zoning system supports educational equity, it requires continuous evaluation and refinement to optimize its impact in diverse urban settings like Jakarta.